Topology of diffusion changes in corpus callosum in Alzheimer's disease: An exploratory case-control study - Kumar, Sumeet; De Luca, Alberto; Leemans, Alexander; Saffari, Seyed Ehsan; Hartono, Septian; Zailan, Fatin Zahra; Ng, Kok Pin; Kandiah, Nagaendran (Frontiers in Neurology, 2022)
Aim: This study aims to assess the integrity of white matter in various segments of the corpus callosum in Alzheimer’s disease (AD) by using metrics derived from diffusion tensor imaging (DTI), diffusion kurtosis imaging (DKI) and white matter tract integrity model (WMTI) and compare these findings to healthy controls (HC). Methods: The study was approved by the institutional ethics board. 12 AD patients and 12 HC formed the study population. All AD patients were recruited from a tertiary neurology memory clinic. A standardized battery of neuropsychological assessments was administered to the study participants by a trained rater. MRI scans were performed with a Philips Ingenia 3.0T scanner equipped with a 32-channel head coil. The protocol included a T1-weighted sequence, FLAIR and a dMRI acquisition. The dMRI scan included a total of 71 volumes, 8 at b = 0 s/mm2, 15 at b = 1000 s/mm2 and 48 at b = 2000 s/mm2. Diffusion data fit was performed using DKI REKINDLE and WMTI models. Results and discussion: We detected changes suggesting demyelination and axonal degeneration throughout the corpus callosum of patients with AD, most prominent in the mid-anterior and mid-posterior segments of CC. Axial kurtosis was the most significantly altered metric, being reduced in AD patients in almost all segments of corpus callosum. Reduced axial kurtosis in the CC segments correlated with poor cognition scores in AD patients in the visuospatial, language and attention domains.